Diversity of plants used in traditional medicine against the main symptoms of COVID-19 in sub-Saharan Africa: review of the literature - Vroh, Bi Tra Aimé (Ethnobotany Research and Applications, 2020)
Background: COVID-19, a deadly disease caused by a new coronavirus (SARS-CoV-2), is affecting sub-Saharan Africa and other parts of the world. Currently, the disease has no treatment (drug or vaccine) and many laboratories are searching for molecules especially based on herbal, to combat COVID-19. The present study allowed to identify the plants usually used in sub-Saharan Africa against coughs, fever and fatigue which constitute the three most frequent symptoms of the disease. Methods: The study was based on a literature review about traditional knowledges on the uses of all plant species against the three symptoms of the disease in sub-Saharan Africa. Results: This review shown that 99 species are used against these three symptoms and various other less common signs of the disease, in 16 sub-Saharan Africa countries. Among these species, 14 like Zingiber officinale, Lippia javanica, Ocimum gratissimum, Citrus limon and Artemisia afra, are current uses in traditional medicine in several countries of the region. Conclusion: The African sub-Saharan region disposes of many plants that can be promising against fatigue, fever and coughs. Additional research could be promoted to assess the safety and clinical value of the main active compounds from these plants and to clarify their actions mechanisms in the case of COVID-19. Key words: COVID-19, medicinal plant, ethnopharmacology, traditional knowledge